The role of ethnic and linguistic issues in the integration and disintegration of modern-age Silesia (the sub-period between 1618/48 and 1740) - Dębicki, Jacek (Publishing House eBooki.com.pl, 2014)
The matter of changes in the ethno-linguistic relations in Silesia evokes a significantly more emotional response from later scholars than those from said period. Contemporary sources approached the issue in a roundabout way or simply marginalised it. Simultaneously, the Silesians considered themselves to be ethnically, possibly also linguistically, to be distinct from the denizens of neighbouring regions. Nonetheless certain categories relating to the territorial outreach of ethno-linguistic groups held true for Silesia. In this context one can distinguish a division formed at the dawn of renaissance, dividing Silesia into the left and right shore of the Oder river. This article concerns the Silesian border regions as well. Other aspects are considered as well, ethno-linguistic aspects capable of negating or furthering divisions in Silesia, aspects such as literary works, teaching and usage of language, (German, Polish, Latin) the presence of Polish printed works, as well as Jewish presence. Deliberations on the subject led to the conclusion that the effect of ethno-linguistic relations on the cohesiveness of Silesian society in the late Habsburg era was rather harmless.
Keywords: borderland; language; dialects; disintegration; integration; ethnicity